Black ballerinas : my journey to our legacy - Copeland, Misty; Barnes, Salena (New York : Aladdin, 2021)
Award-winning author and American Ballet Theatre principal dancer Misty Copeland celebrates dancers of color who have influenced her on and off the stage.
Publishers Weekly, September 2021
Kirkus Starred, October 2021
5-8.
1240L
7.4
Keywords: African American ballerinas -- Biography -- Juvenile literature; Ballerinas -- United States -- Biography -- Juvenile literature; African American ballerinas; Ballerinas; Women; Biographies; African Americans -- Biography